THE APPLICATION OF ADVERTISEMENTS FOR TEACHING VOCABULARY AT SMA LPP UMI (Karya Ilmiah Mahasiswa (KIMA), 2022)
The purpose of this study was to measure the effectiveness of the use of advertisements in learning vocabulary in the ten graders of SMA LPP-YW UMI and to determine students' perceptions of the use of advertisements in learning vocabulary in the ten graders of SMA LPP-YW UMI. The researcher applied a pre-experimental method with a one group pre-test and post-test design, and collected data based on the test. The sample of this research is the students of class X SMA LPP-YW UMI Makassar, totaling 18 students. Samples were taken using total sampling technique. The results showed that the results of the pre-test scores of second graders increased significantly after being taught using the advertising method. The average value obtained through the pre-test was 43.68 and the posttest was 68.89 with the result that the significance value of the paired sample test was smaller than the significance level of 0.000